NATURAL RADIOACTIVITY AND ASSESSMENT OF THE INTERNAL DOSE OF WATER RESOURCES FOR SELECTED SITES IN EGYPT - Atef, Amira; El Begawy, Hekmat Mohamed; Arafat, Ashraf Ali; Zaher, Ebtsam Rizq; Fahmy, Enayat Ebrahim (International Journal of Environmental Sciences, 2019)
Purpose: The current study aims to assess the activity concentrations of 226Ra (238U series), 232Th series and 40K in different water resources in Egypt to determine its applicability for drinking process from the radiological view point. Methodology: Forty five water samples (15 tap water samples, 15 ground water samples and 15 surface water samples) from selected sites in the area under investigation (along the Northern part of Egypt from Sinai governorate in the East to Marsa Matrouh governorate in the West) were analyzed using HPGe detector. The data obtained were used to calculate the annual dose for different organs from consumption of water for four age groups (5 years, 10 years, 15 years and adults) using AcuteDose calculator program. Findings 40K is the only detected while 226Ra and 232Th in all samples under investigation are below the detection limit (0.7 and 0.6 Bq kg-1 respectively) of the used HPGe detector. The mean concentration from tap water is 1.06 BqL-1 and values ranged from < 3 to 5.30 Bq L-1. Ground water showed a mean of 1.01Bq L-1 and values ranged from < 3 to 5.16 Bq L-1 and in surface water, the mean was 3.16 Bq L-1 and values ranged from < 3 to 32.09 Bq L-1. For all water resources, the lower the age is the higher the dose delivered from 40K in water. For tap water, the highest annual dose delivered to 5 y age group (6.16 µSv y-1) with a mean of 1.32 µSv y-1 and the lowest annual dose was delivered to adults with a maximum of 1.79 µSv y-1 and a mean of 0.33 µSv y-1. For ground water, the highest annual dose (6.12 µSv y-1) delivered to 5 y age group with a mean of 1.35 µSv y-1, and the lowest annual dose was delivered to adults with a maximum of 1.71 µSvy-1 and a mean of 0.34 µSv y-1. All results of this work are below the maximum permissible limit for public exposure determined by ICRP. Unique contribution to theory, practice and policy: Government and stakeholders should make funds available for more research to study the applicability of these water resources for drinking process from other points view such as chemical and biological toxicity.